2015
DOI: 10.1111/jnc.13058
|View full text |Cite
|
Sign up to set email alerts
|

Tripchlorolide ameliorates experimental autoimmune encephalomyelitis by down‐regulating ERK1/2‐NF‐κB and JAK/STAT signaling pathways

Abstract: Tripchlorolide (T4), an extract of the natural herb Tripterygium wilfordii Hook F, has been found to possess anti-inflammatory and immunosuppressive actions. In the current study, these actions were evaluated in experimental autoimmune encephalomyelitis (EAE), an animal model of multiple sclerosis by scoring the clinical signs, observing the infiltration of inflammatory cells and myelin sheath in the lumbar spinal cord of EAE mice. The results demonstrated that T4 (at a dose of 40 lg/kg) significantly reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Moreover, CCH induces memory impairment and accelerates A β generation [9, 53]. Interestingly, TRC produces anti-inflammatory effects by downregulating extracellular signal-regulated protein kinases 1/2 (ERK1/2) nuclear factor kappa-light-chain-enhancer of activated B cells (NF- κ B) and JAK/STAT signaling pathways [24, 54]. TRC also attenuates A β generation by inhibiting BACE1 activity and protects neurons against microglia-mediated A β neurotoxicity by suppressing NF- κ B and JNK signaling [23, 25].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CCH induces memory impairment and accelerates A β generation [9, 53]. Interestingly, TRC produces anti-inflammatory effects by downregulating extracellular signal-regulated protein kinases 1/2 (ERK1/2) nuclear factor kappa-light-chain-enhancer of activated B cells (NF- κ B) and JAK/STAT signaling pathways [24, 54]. TRC also attenuates A β generation by inhibiting BACE1 activity and protects neurons against microglia-mediated A β neurotoxicity by suppressing NF- κ B and JNK signaling [23, 25].…”
Section: Discussionmentioning
confidence: 99%
“…Berberine (BBR), an isoquinoline alkaloid derived from plants, also ameliorated EAE symptoms through a mechanism involving inhibition of JAK/STAT signaling in Th1 and Th17 cells, as well as reduced production of IL-6 by innate immune cells [141]. Similar studies have demonstrated the efficacy of other natural compounds, such as Tripchlorolide [142], Quercetin [143], and vitamin D3 [144], in ameliorating EAE through inhibition of JAK/STAT signaling and Th1 and Th17 differentiation.…”
Section: Therapeutic Value Of Inhibitors Of Jak/stat Signaling In mentioning
confidence: 99%
“…A recent study by Zhang et al reported that tripchlorolide (T4), an extract of the natural herb Tripterygium wilfordii Hook F (TWHF), reduces the severity of EAE and inhibits ongoing disease by suppressing the JAK2/STAT1/ STAT3 axis. 147 Additionally, another study using an EAE model in rats demonstrated that cornel iridoid glycoside (CIG), the main component extracted from Cornus officinalis , reduced disease severity, incidence, disease onset and ongoing paralysis through blocking the JAK/STAT1/3 axis in the brain 148 (Table 1). …”
Section: The Jak/stat Pathway As a Promising Therapeutic Target mentioning
confidence: 99%